(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the artistic representation of psychological states in the short stories of Rahnavard Zaryab, one of the most prominent representatives of modern Afghan literature. The study focuses on the depiction of inner conflicts, emotional experiences, and psychological transformations in the stories “The Enchanted City,” “The Cry,” “The Dagger,” and “The Dancer.” Through textual and comparative literary analysis, the research explores the narrative techniques employed by the writer and identifies similarities and differences between Zaryab’s works and selected stories by the Uzbek writer Abdullah Qahhor. The findings reveal that psychological portrayal constitutes one of the defining features of Zaryab’s artistic style. The author successfully depicts human emotions through symbolism, internal monologue, landscape imagery, and psychological dialogue. The study contributes to a deeper understanding of psychological prose in Afghan literature.